2017
DOI: 10.1158/1078-0432.ccr-16-0979
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Androgen Receptor in Patients with Early-Stage Breast Cancer: A Meta-analysis of Clinical and Gene Expression Data

Abstract: Purpose: Androgen receptor (AR) expression has been observed in about 70% of patients with breast cancer, but its prognostic role remains uncertain.Experimental Design: To assess the prognostic role of AR expression in early-stage breast cancer, we performed a metaanalysis of studies that evaluated the impact of AR at the protein and gene expression level on disease-free survival (DFS) and/or overall survival (OS). Eligible studies were identified by systematic review of electronic databases using the MeSH-ter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
85
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 68 publications
11
85
2
3
Order By: Relevance
“…Breast cancer is the most frequent cancer in women [23]. Although endocrine therapy, targeting therapy and chemotherapeutics have greatly improved the overall survival of breast cancer patients, the drug resistance is the main clinical problem [24].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most frequent cancer in women [23]. Although endocrine therapy, targeting therapy and chemotherapeutics have greatly improved the overall survival of breast cancer patients, the drug resistance is the main clinical problem [24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis in which AR mRNA expression was correlated with various gene signatures in large combined breast cancer cohorts strongly supports this concept (26). Functionally, AR and ERa are hormone-activated nuclear transcription factors that regulate gene expression and are commonly coexpressed in normal and malignant breast epithelial cells (37,56), indicating the potential for direct cross-talk between these two sex hormone receptor signaling pathways.…”
Section: Discussionmentioning
confidence: 90%
“…Disparate results among studies may be attributed to heterogeneity of breast cancer cohorts and differences in methodology, including the use of different cut-points for AR positivity. Although several meta-analyses commonly conclude that AR is associated with better outcomes in ERa-positive disease (26)(27)(28)(29), these analyses used population-level rather than individual patient-level data. Moreover, most studies included in the meta-analyses of AR as a prognostic biomarker used cut-points that are typically those used for ERa and progesterone receptor (PR) as a predictive biomarker (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…The prognostic role of AR in ER+ BC has been extensively studied. Several authors have reported that AR expression in luminal cancers is associated with a better outcome compared to AR negative BCs (Park et al 2011, Castellano et al 2013, Kim et al 2015, Bozovic-Spasojevic et al 2016. However, some reports suggest that AR could be related to BC progression (Grogg et al 2015), as it is detected in a significantly higher percentage of ductal carcinomas 'in situ' (DCIS) that are adjacent to invasive carcinomas than in pure DCIS (Yu et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…AR positivity has been detected in up to 61% of primary and metastatic BC lesions (Park et al 2010, Hu et al 2011, Yu et al 2011) and approximately 75% of ER-positive (ER+) BCs are also AR positive (AR+). Several studies have shown that AR expression in luminal tumours (ER+) is associated with lower tumour grade, smaller tumour size, lower proliferative index (Ki67 level) and more importantly, AR expression in ER+ tumours is an independent prognostic factor of a good outcome (Castellano et al 2010, Niemeier et al 2010, Aleskandarany et al 2016, Bozovic-Spasojevic et al 2016). On the other hand, up to 31% of ER-negative (ER−) BCs are reported to be AR+ (Niemeier et al 2010, Park et al 2010, but the prognostic impact of AR expression in this subset of BCs is not clear (Luo et al 2010, Hu et al 2011, Park et al 2011, Pistelli et al 2014, Vera-Badillo et al 2014, Hilborn et al 2016, Jiang et al 2016, Asano et al 2017.…”
Section: Introductionmentioning
confidence: 99%